STRATEGIES FOR AGRONOMIC BIOFORTIFICATION OF POTATO TUBERS WITH ZINC - Kumar, Prince (Potato Journal, 2022)
Current study explored the possibility of increasing zinc (Zn) content in potato tubers by foliar, seed tubersoaking, and soil application of Zn fertilizers. During first year, a single application of 5 kg Zn ha-1 through zinc sulphate(ZnSO4) increased the Zn concentration by ~30 % followed by split application of ZnSO4 (19.6%), and a single applicationof 1 kg Zn as Zn-EDTA (17.6%) in whole tubers. Single and split soil application of either zinc sulphate (5 kg ha-1) orzinc-EDTA (1.0 kg Zn ha-1), foliar application (ZnSO4) and soaking of seed tubers in zinc sulphate solution before plantingalso increased its concentration significantly in tuber peels. During 2nd year of experimentation, a single soil applicationof zinc sulphate (5 to 10 kg Zn ha-1), Zn-EDTA (1 to 2 kg Zn ha-1) increased the Zn concentration in peeled (tuber flesh)as well as unpeeled whole tuber significantly. Application of 2 kg zinc as Zn-EDTA resulted in highest increase of 4.4 mgkg-1 Zn (25.7%) in tuber flesh which was comparable with 10 kg Zn as ZnSO4 (24.9%). On application rate basis, comparedto ZnSO4, the 5-times lesser quantity of chelated Zn resulted in equivalent increase in tuber Zn concentration. Since, thebioavailability of Zn from potatoes is high, the soil application of Zn fertilizers during the initial crop growth stage, asrevealed by this study, can be adopted as a simple strategy to increase its content in tubers for addressing Zn - relatedmalnutrition issues.